Segmentacja porównawcza gospodarstw domowych na różnych rynkach ubezpieczeń - Batóg, Barbara; Mojsiewicz, Magdalena; Wawrzyniak, Katarzyna (The Comparison of Results of the Segmentation of Households on Different Insurance Markets, 2008)
In the article the authors tries to verify the hypothesis that groups of customers with similar behaviour, discriminated on different insurance markets, coincide in a great degree. It means that the customer behaving rationally on the property insurance market behaves rationally also on the other insurance markets. On that account the research was conducted in two stages. In the first stage a group of rational customers was separated accordingly to the Wagner theory. In the second stage the segmentation of customers was made. This segmentation was compared to the group of rational customers. Statistical data came from the survey of 500 respondents (heads of households) conducted in 2006 in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 390-398